2017
DOI: 10.1071/hc16062
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of patients with multimorbidity: a qualitative study of patients’ and supporters’ views

Abstract: INTRODUCTION Multimorbidity impacts on patients' health and wellbeing, but relationships experienced within social networks can support people to live well. AIM This study sought to elicit the views of New Zealanders with multimorbidity about their social networks and the views of their nominated supporters. METHODS Ten patients with multimorbidity and their nominated supporters each independently recorded their views of the patient's social network on a five-concentric-circle template, indicating supporting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…29 CoCPs can also include student-learners who join temporarily in pursuit of their education. 18,21,30 Social network researchers often use mapping tools for people to record their supporters, including patients with long-term conditions or multimorbidity. 8,9,12,16 Mapping tools typically include a template with concentric circles indicating the relative importance of supporters to the person, who is in the centre.…”
Section: Context Of Research Social Network Theory and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 CoCPs can also include student-learners who join temporarily in pursuit of their education. 18,21,30 Social network researchers often use mapping tools for people to record their supporters, including patients with long-term conditions or multimorbidity. 8,9,12,16 Mapping tools typically include a template with concentric circles indicating the relative importance of supporters to the person, who is in the centre.…”
Section: Context Of Research Social Network Theory and Toolsmentioning
confidence: 99%
“…16 Some social networks include general practice and other health professionals. 17,18 These networks are akin to Communities of Clinical Practice (CoCP), whereby a group of people, both professional and lay, commit to providing support for particular patients. 11,[19][20][21] General practice teams believe they are the health-care anchor to coordinate care for patients with long-term conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Using a five-concentric-circle social network mapping template (modified from E & B Wenger-Trayner (Wenger-Trayner & Wenger-Trayner, 2015)), patients, together with students, mapped their social network and recorded their relative importance to the patient by recording proximity of each to the centre of the circle. These results are presented elsewhere (McKinlay, McDonald, Darlow, & Perry, 2017).…”
Section: Contextmentioning
confidence: 58%
“…For instance, in a study by Hawkley et al, it was concluded that particularly the quality of relationships is a key determinant of loneliness. 42 The study showed that patients with multimorbidity have a rich and diverse social network; however, some of the nominated supporters are not aware of their important role that may indicate a rather one-sided relationship and a possible negative perception of one's own social network. 41 Further explanation for the results of this study might be provided by a qualitative study from New Zealand.…”
Section: Relation To Previous Research and Possible Explanationsmentioning
confidence: 93%
“…The authors stated that health professionals either underestimated their importance in their patient's social network or did not want to be too important to the patient. 42 The study showed that patients with multimorbidity have a rich and diverse social network; however, some of the nominated supporters are not aware of their important role that may indicate a rather one-sided relationship and a possible negative perception of one's own social network. This insight might explain why the onset of multimorbidity leads to an increased social network but also increased loneliness.…”
Section: Relation To Previous Research and Possible Explanationsmentioning
confidence: 93%